The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1017/s095457941400087x
|View full text |Cite
|
Sign up to set email alerts
|

Risk and resilience in preterm children at age 6

Abstract: Children born preterm are at risk for experiencing significant deleterious developmental outcomes throughout their childhood and adolescence. However, individual variation and resilience are hallmarks of the preterm population. The present study examined pathways to resilience across multiple domains (e.g. social activities, peer relations, ADHD symptomology, externalizing and internalizing behavior, sleep quality) as children born preterm reached school age. The study also examined early child and family pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 81 publications
2
44
3
2
Order By: Relevance
“…Previous studies showed that preterm children have difficulties with inhibitory control [8] and that these predict later learning and attention problems [21,22]. Our results suggest a dose-response effect of low gestational age at birth on inhibitory control across the whole GA 9 spectrum.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies showed that preterm children have difficulties with inhibitory control [8] and that these predict later learning and attention problems [21,22]. Our results suggest a dose-response effect of low gestational age at birth on inhibitory control across the whole GA 9 spectrum.…”
Section: Discussionsupporting
confidence: 59%
“…A recent study suggested that inhibitory control might predict learning and attention regulation abilities at age six years in preterm children [21]. Others have shown that very preterm children have problems with inhibitory control [8] and that these may be associated with delay of frustration as well as attention and behavior problems in preadolescence [22].…”
mentioning
confidence: 99%
“…Maternal depression, parent-child interactions, child dysregulation, and socioeconomic challenges are risk factors that have long been viewed as critical to children’s development within preterm populations 4,36 . Although one would expect observations of expressed negative affect, emotional lability, irritability, and impulsivity to relate to externalizing behavior, dysregulation was also associated with trajectories of internalizing behaviors, suggesting that children in Group 1 (High) for either trajectory may experience more generalized underlying difficulties in regulation and emotional control, and that such difficulties are evident early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Families who did not participate in the study at 6 years of age had fewer sociodemographic assets and were less likely to be Caucasian (Table 1; see Poehlmann-Tynan et al, 2015 for more details). 22 This attrition pattern may limit the study generalizability and the presented findings may not reflect non-Caucasian families or those with fewer sociodemographic assets. Finally, the bidirectional nature of sleep and developmental/health concerns should be acknowledged.…”
Section: Discussionmentioning
confidence: 90%
“…Participant family characteristics paralleled the population of the region in education and poverty, although participant families were more racially diverse (for additional details see Poehlmann-Tynan et al, 2015). 22 Additional descriptive statistics are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%